2023
DOI: 10.1038/s41598-023-31616-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial for comparing the efficacy of desensitizing toothpastes on the relief of dentin hypersensitivity

Abstract: The 4-week double-blind clinical trial to manage dentin hypersensitivity (DH) using different desensitizing toothpastes was conducted. 53 participants with DH were enrolled in this trial. The participants were randomized into 3 groups: Group N; no active ingredient-containing toothpaste (Pleasia fluoride-free), Group SC; a toothpaste containing strontium chloride (Sensodyne Original), and Group TP; a toothpaste containing tricalcium phosphate (Vussen S). They were instructed to brush their teeth manually for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…Dionysopoulos et al [7] review contemporary therapeutic approaches to dentin hypersensitivity, emphasizing the long-term benefits of tubule occlusion, particularly through the use of bioactive materials like calcium phosphate and nano-hydroxyapatite. This occlusion can be achieved with various ions, such as strontium or calcium ions and phosphate anions [8]. These substances are found in materials like amorphous calcium phosphate (ACP), tricalcium phosphate (TCP), nano-hydroxyapatite (nHA), bioactive glasses, among others.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dionysopoulos et al [7] review contemporary therapeutic approaches to dentin hypersensitivity, emphasizing the long-term benefits of tubule occlusion, particularly through the use of bioactive materials like calcium phosphate and nano-hydroxyapatite. This occlusion can be achieved with various ions, such as strontium or calcium ions and phosphate anions [8]. These substances are found in materials like amorphous calcium phosphate (ACP), tricalcium phosphate (TCP), nano-hydroxyapatite (nHA), bioactive glasses, among others.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of these materials, their size and potential criticality are very important, as they may affect the ability to deliver ions and the depth of ion penetration into the lesion. For this reason, different products have different mineralization effects [8,9]. Research has demonstrated the capacity of bioactive glass not only to deliver critical ions for remineralization but also to initiate the formation of hydroxy carbonate apatite (HCA), which closely resembles the mineral composition of natural teeth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the numerous methods proposed for treating DH, a definitive solution to the issue has yet to be identified. Clinical studies evaluating the efficacy of different treatment approaches yield contradictory results [10][11][12]. This discrepancy stems from the fact that all these studies assess pain intensity, a parameter that proves notably challenging to evaluate due to its inherently subjective and intricate nature [13].…”
Section: Introductionmentioning
confidence: 99%